The Influence of Internal and External Factors on Profits of Sharia Life Insurance Units in Indonesia (2016-2020 Period) - Tini Anggraeni; Zakiyyatun Nafilah (AL-FALAH : Journal of Islamic Economics, 2022)
Purpose: This study aims to analyze the long-term and short-term impact and influence of premiums, investment returns, inflation and exchange rates on Islamic insurance companies.Design/Method/Approach: This research uses associative which aims to determine the relationship of two or more variables with a quantitative approach. The data collection technique is by using the financial statements of each life insurance company in the sharia business unit. In addition, this study also uses data from government publication reports such as OJK, Bank Indonesia and BPS. The method used is panel data regression and ARDL to determine the long-term and short-term effects.Findings: The results show that from several companies sampled in the study, it is known that the companies that have the most influence on premiums, investment returns, inflation and exchange rates on sharia life insurance profits are PT. Prudential Life Assurance. This is because based on the company's financial statements the premium rate at PT. Prudential Life Assurance since 2016-2020 continues to increase significantly every year. Based on the ARDL method, it is known that in the short term all variables have a significant effect on profits, while in the long term premiums and the exchange rate have a significant effect on profits while investment and investment returns have no effect on profits in the long term.Originality/Values: The contribution of this research can provide information and be used as a reference in research on the analysis of the influence of internal factors and external factors on the profit of Islamic life insurance in Indonesia. In addition, it is hoped that this research will be used as a reference material in determining the decision to use a company's insurance services and with this research it is expected to be a reference for the government to be able to improve the sharia life insurance industry in its development.